(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: Rheumatoid arthritis (RA) is a progressive autoimmune inflammatory disease affecting 1% of the population .Aim and objective: Study designed to determine the role of Tumor Necrosis Factor alpha (TNF- α )in a group of patients with rheumatoid arthritis for specific period of time and healthy controls. Subjects and methods: Blood samples were taken from 68 patients with rheumatoid arthritis Hospital in Thi-Qar province/Iraq and 20 healthy controls. All the information were taken from the patients and controls. An Enzyme-linked immunosorbent assay was used for estimation TNF-α . Results: The study showed that females are more susceptible to RA than males. Also the study showed common age group between (41-50) years of age was more than other groups. TNF-α showed a significant increase in RA patient compared to a healthy peoples . The mean of TN-α in patient was (41.6 ± 14.1) while in control (5.16 ± 1.58) ,in male patient and control mean was (45.9 ± 13.8),(4.88 ± 1.48 ) while in female patient and control mean was (41.2 ±13.7),(5.26 ±1.65) respectively. Conclusions: The study conclude that the levels of TNF-α play the important role in patients with RA, also TNF-α is the initiator of inflammation associated with the disease .The genetic factors may have a vital role to progression the RA.